Climate Change and Health - Fraser S (Journal of Multidisciplinary Healthcare, 2025)
Scott Fraser Editor in Chief Journal of Multidisciplinary Healthcare, Sunderland, UKCorrespondence: Scott Fraser, Email sgfraser@icloud.com